Rethinking migration through public-private partnerships in the Mediterranean - Pacillo, Grazia; Savelli, Adam; Zaccari, Claudia (2025)
At this year’s MED – Mediterranean Dialogues in Naples, the Migration Forum which held on October 15 cut to the chase. With public budgets shrinking, participants asked how to turn policy into investable pathways for mobility. Conversations explored in depth serious public-private partnerships and research-guided choices that can improve well-being and integration, address root pressures in places of origin, and protect people en route.